2023
DOI: 10.1186/s12884-023-05456-1
|View full text |Cite
|
Sign up to set email alerts
|

Unique microRNA expression profiles in plasmic exosomes from intrahepatic cholestasis of pregnancy

Abstract: Background Intrahepatic cholestasis of pregnancy (ICP) is strongly associated with an increased risk of adverse perinatal outcomes. Total bile acid (TBA) levels in the late second or third trimester are a major factor in the diagnosis. Here, we sought to establish the miRNA expression profile of plasm exosomes of ICP and identify possible biomarkers for the diagnosis of ICP. Methods This case–control study involved 14 ICP patients as the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
0
0
Order By: Relevance
“…In a recent study, the researchers identified that three miRNAs (miR-940, miR-636, and miR-767-3p) were upregulated in the plasma exosomes of patients with ICP. Additional analysis revealed that the AUC values of miR-940, miR-636, and miR-767-3p were 0.7591, 0.7727, and 0.8955, respectively (Kong et al, 2023). Taken together, these study findings suggest the higher diagnostic accuracy, sensitivity, and specificity of a combination of miRNAs.…”
Section: Diagnostic Value Of Mirnas In Icpmentioning
confidence: 59%
“…In a recent study, the researchers identified that three miRNAs (miR-940, miR-636, and miR-767-3p) were upregulated in the plasma exosomes of patients with ICP. Additional analysis revealed that the AUC values of miR-940, miR-636, and miR-767-3p were 0.7591, 0.7727, and 0.8955, respectively (Kong et al, 2023). Taken together, these study findings suggest the higher diagnostic accuracy, sensitivity, and specificity of a combination of miRNAs.…”
Section: Diagnostic Value Of Mirnas In Icpmentioning
confidence: 59%